Changes in ownership structure - Masulis, Ronald W. (Journal of Financial Economics, 1987)
This study analyzes both the causes and effects of mutual S&L conversions to corporate charter. Changes in technology and government policies have substantially increased S&L competition, riskbearing, and potential scale and scope economies. Evidence indicates that these changes have decreased the relative operating advantages of mutual S&Ls, encouraging conversions to stock charter. The S&L's financial and operating characteristics, which affect the success of the conversion effort, are also explored.